Assessement of Glifosat herbicide to viability of decomposer B Com T isolate in vitro - Donny Nugroho Kalbuadi; Muhammad Abdul Azis; Aris Lukito; Lydia Ayu Utami; Salsa Bila Alzahra; Khansa Destiandani; Happy Widiastuti (Indonesian Sugar Research Journal, 2026)
Sugarcane plantation produces approximately 10 to 12 tons of trash per hectare in a single growing season. The high content of lignin and cellulose in the litter necessitates the use of decomposers to accelerate the decomposition process, thereby enhancing the benefits of trash application to soil fertility and plant growth. However, decomposers are microorganisms whose effectiveness is influenced by their viability in the field. In sugarcane land management practices, herbicide application is performed to control weeds during the 1-2 month growth phase of sugarcane/ratoon. This study aimed to evaluate the in vitro resistance of the B-Comp T decomposer isolate to glyphosate herbicide. B-Comp T is a microbial consortium comprising one cellulolytic fungus (Trichoderma sp.), two lignolytic fungi (LGT1 and Omphalina sp), one lignolytic bacteria (LT5), and two cellulolytic bacteria (S sereh and SPC 5). The experiment was conducted using Petri dishes with PDA medium for fungi and NA medium for bacteria. Glyphosate herbicide concentrations tested were 0%, 0.03%, 0.06%, 0.12%, and 0.15%, which were incorporated into the medium during sterile medium pouring into Petri dishes. Fungi incubation was carried out for 7 days while 5 days for bacteria. Microbial growth was observed visually. The observation results demonstrated that the effect of glyphosate on microbial growth varied among species, as did their tolerance limits. At low concentrations, glyphosate generally stimulated microbial growth, whereas at high concentrations, it inhibited microbial growth. Among the tested decomposer isolates, the bacterial isolates LPC 2 and SPC 5 exhibited resistance to glyphosate, while the most susceptible isolate was lignolytic wite rot fungi Omphalina sp and cellulolytic bacteria S. sere.